The Influence of Instructor Competencies and Work Motivation on Instructor Performance and Its Implications on the Quality of Graduates (Survey on Flight Operation Officer (FOO)) - Gunawan, Asep; Suwandi, Yudi Wahyudin (Maneggio, 2025)
This study aims to analyze the influence of instructor competence and work motivation on instructor performance and its implications on the quality of graduates with a case study on Flight Operation Officer (FOO). The method used is quantitative with a survey approach. A total of 83 respondents who were FOO instructors were used as research samples. The data analysis technique uses path analysis to test the direct and indirect relationships between variables. The results of the study show that the competence of instructors has the greatest influence on instructor performance, both directly and indirectly through work motivation. Work motivation has also been shown to have a significant effect on improving instructor performance. Simultaneously, competence and motivation contribute significantly to instructor performance, and instructor performance has been shown to have strong implications for the quality of graduates. This finding confirms that improving the competence and motivation of instructors is a strategic factor in ensuring the quality of graduates in the field of aviation operations.